RELATIONSHIP BETWEEN MOTHERS’ KNOWLEDGEAND ATTITUDES ABOUT GIVING MR IMMUNIZATION - Prajamukti, Ahmad Yudistira; Kusyani, Asri; Aziz, Aditya Nuraminudin (LPPM STIKes Bahrul Ulum Jombang, 2020)
The case of Measles and Rubella (MR) in children is a major problem in the health sector especially in Indonesia which requires effective prevention. According to WHO in the Indonesian Ministry of Health 2018, in 2017 the number of MR infections in the world reached around 190,000 cases. Meanwhile, from 2015 to 2017 in Indonesia, MR immunization decreased by 61.8% (Ministry of Health, 2018). In line with case, the purpose of this study was to determine the relationship between mothers’ knowledge and attitudes about giving MR immunization. This study used the Literature Review method with a journal search process. Full-text articles were obtained from a database, Google Scholar, using keywords; knowledge of MR immunization, mothers’ attitudes about MR, and MR immunization. Journals were taken by researchers, published in the period 2015-2020 with a total of 10 journals. The results of this study concluded that from 9/10 journals explained there is a relationship between knowledge and attitudes of mothers towards MR immunization. Furthermore, just only 1 journal explains there is no relationship between knowledge and attitudes of mothers towards MR immunization. The researcher suggests that the head of the public health center could do a work plan about counseling measles-rubella immunization to make society realize that it is the important thing.